Penerapan model pembelajaran kooperatif tipe stad dipadukan dengan snowball throwing untuk meningkatkan keterampilan sosial - Muhammad Bayu Aji; Sukarno Sukarno; Kartono Kartono (Didaktika Dwija Indria, 2019)
The purpose of this research were to improve the social skill through Cooperative Learning Model Students Teams Achievement Divisions(STAD) combined with Snowball Throwing to 5th grade students of Sendanglo Boyolali State Islamic Elementary School in the academic year of 2016/2017. This research were conducted in two cycles, each cycle consisting of planning, action, observation, and reflectioin. The subject of this research were the teacher and students of 5th grade in Sendanglo Boyolali State Islamic Elementary Shcool. The data collecting techniques of this research are observation, interview, and documentation. The data validity of this research is tested using source triangulation. The data analysis technique used is interactive analysis model. The result of this research was shown that implementation of Cooperative Learning Model STAD combined with Snowball Throwing can improve social skill. This evidenced by increasing the result of observation social skills in each cycle. On the precycle, frequency attainment of social skill in good and very good categories as much as 6 students (27,7%). On the firsy cycle, increased to 13 students (59,09%). On the second cycle, increased to 20 students (91%). Based on the analysis of the result, it can be concluded that implementation of Cooperative Learning Model STAD combined with Snowball Throwing can improve the social skill of the 5th grade students of Sendanglo Boyolali State Islamic Elementary School in the academic year of 2016/2017